Tanggapan Tanaman Kedelai terhadap Inokulasi Rhizobium - PURWANINGSIH, OKTI; INDRADEWA, DIDIK; KABIRUN, SITI; SHIDDIQ, DJAFFAR (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012))
Nitrogen is one important element in plant growth. In soybean crop nitrogen requirement can be met from the fixation of nitrogen which is the result of symbiosis between rhizobium bacteria with soybean. A study on the relationship between soybean cultivar and rhizobium inoculation was conducted in Banguntapan Bantul Yogyakarta on regusol soils. Research aimed the responses of soybean cultivar of rhizobium inoculation. This research is a pot experiment that tested the response of 16 soybean cultivars of rhizobium inoculation. The sixteen cultivars consisted of 12 superior cultivars and 4 local cultivars. Before planting soybean seeds were inoculated with legin. Land used first sterilized using autoclaves. Determination of soybean cultivars into four categories based on agronomic characters nodule number, nodule dry weight, canopy N content, nitrogenase activity and grain yield components (seed dry weight). The study demonstrated that (1) Cultivars Anjasmara, Sibayak, Surya, Gepak yellow, Galunggung, Argomulyo and Baluran provide a response to rhizobium inoculation in the form of increased nitrogen fixation and grain yield (2) rhizobium inoculation on Tanggamus cultivars can increase nitrogen fixation but not followed by an increase in grain yield (3) rhizobium inoculation in cultivar Malabar, Seulawah and Petek not increase nitrogen fixation but can increase grain yield (4) rhizobium inoculation in cultivar Ijen, Sinabung, Wilis, Grobogan, and Garut not increase nitrogen fixation and grain yield.
Keywords: soybean, rhizobium